(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2020)
Article 136 of the Russian Constitution provides for a special (“aggravated”) procedure for the adoption of the constitutional amendments. However, the constitutional-reform bill of 2020, which has been passed recently in a matter of days by the national parliament and the regional legislatives, has established an ad hoc procedure for the adoption of Amendments. The Russian President’s willingness to ignore and bypass the Constitution’s amendment provisions, comforted by the legislative body, casts a shadow over the legitimacy of this reform. At the same time, an inconsistent and discretionary application of the procedural norms is not something new in the Russian law-making process, since the “adjustment” of the legislative drafting procedures has become through time an increasingly consolidated practice. That could happen due to the lack of a complete and detailed regulatory framework aimed at securing proper procedures for amending the constitution. Therefore, the regulation of this very sensitive issue occurs, to a large extent, within Chambers’ Rules. Thus, inevitably, the whole procedure suffers from numerous defects.